Computation offloading technique for energy efficiency of smart devices - Ko, Jaejun; Choi, Young June; Paul, Rajib (Journal of Cloud Computing, 2021)
The substantial number of wearable devices in the healthcare industry and the continuous growth of the market procreates the demand for computational offloading. Despite major development of wearable devices and offloading techniques, there are several concerns such as latency, battery power, and computation capability that requires significant development. In this paper, we focus on the fact that most smart wearable devices have Bluetooth pairing with smartphones, and Bluetooth communication is significantly energy-efficient compare to 3G/LTE or Wi-Fi. We propose a computation offloading technique that offloads from the smartphone to the cloud server considering the decision model of both wearable devices and smartphones. Mobile cloud computing can elevate the capacity of smartphones considering the battery state and efficient communications with the cloud. In our model, we increase the energy efficiency of smart devices. To accomplish this, a Dhrystone Millions of Instructions per Second (DMIPS)-based workload measurement model along with a computation offloading decision model were created. According to the performance evaluation, offloading from wearable devices to smartphones and offloading once to cloud server can reduce energy consumption significantly.
Keywords: Bluetooth communications; Computation offloading; Decision modeling; Efficient communications; Healthcare industry; Instructions per seconds; Reduce energy consumption; Workload measurements; Computation offloading; Energy efficiency; Smartphone; Wearable device